Staged repair of borderline hypoplastic heart disease with early biventricular conversionCentral MessagePerspective - Nicholas D. Andersen, MD; Douglas M. Overbey, MD; Neel K. Prabhu, MD; Andrew W. McCrary, MD, MSc; Jennifer I. Sherwin, MD; Veerajalandhar Allareddy, MD; Joseph W. Turek, MD, PhD (JTCVS Techniques)
Objective: In select patients with borderline ventricular hypoplasia, we adopted a strategy of initial single-ventricle palliation followed by staged or direct biventricular conversion by 2 years of age. Methods: Between 2018 and 2023, 14 newborns with borderline hypoplastic heart disease deemed high risk for primary biventricular repair underwent palliative procedures as a neonate/infant, followed by staged or direct biventricular conversion. Results: Of the 14 patients, 6 had borderline left ventricles and 8 had borderline right ventricles. Index neonatal operations were performed in 12 patients and included the Norwood operation (n = 5), pulmonary artery band (n = 3), ductal stent (n = 3), and hybrid Norwood (n = 1). Five patients underwent direct biventricular conversion, and the remaining 9 patients underwent staged ventricular recruitment operations at a mean age of 6 months (range, 3-11 months). Ventricular recruitment operations included atrial septation with or without ventricular rehabilitation, atrioventricular valve repair, or outflow tract operations. At a mean duration of 8 months (range, 4-10 months) after ventricular recruitment, there was a significant increase in chamber volume, aortic valve, and mitral valve size in patients with borderline left ventricles, and a normalization of the right ventricle:left ventricle end-diastolic volume ratio in patients with borderline right ventricles. To date, 13 of 14 patients have undergone successful biventricular conversion at a mean age of 16 months (range, 4-31 months). Conclusions: In select newborns with borderline hypoplastic heart disease, single-ventricle palliation followed by staged or direct biventricular conversion may increase infant survival while allowing for early attainment of a biventricular circulation.